1988
DOI: 10.1002/ajmg.1320310226
|View full text |Cite
|
Sign up to set email alerts
|

Severe congenital cutis laxa with pulmonary emphysema: A family with three affected sibs

Abstract: Clinical and morphologic findings in 3 sibs with congenital cutis laxa are presented. A severe urinary malformation in one affected infant is reported in detail. Elevated serum copper concentrations were observed in 2 of the sibs and in the healthy mother. However, the 64Cu uptake of fibroblast cells from tissue culture was not increased. Ultrastructural pathologic findings from skin biopsies have been studied and compared at birth and at age 2 years. The lack of junction between the 2 elastic fiber components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Although we excluded fibulin-5 and fibulin-4 gene mutations in the proband, we cannot formally exclude the possibility of a recessive or digenic inheritance since not all loci for ARCL have been identified. In contrast, pulmonary artery stenosis as seen in the proband can be associated with ARCL [McKusick, 1972;Van Maldergem et al, 1988] but is extremely rare in ADCL where only two cases have been reported [Hayden et al, 1968;Tassabehji et al, 1998]. Pulmonary artery stenosis is frequently associated with ELN haploinsufficiency [Metcalfe et al, 2000].…”
Section: Discussionmentioning
confidence: 82%
“…Although we excluded fibulin-5 and fibulin-4 gene mutations in the proband, we cannot formally exclude the possibility of a recessive or digenic inheritance since not all loci for ARCL have been identified. In contrast, pulmonary artery stenosis as seen in the proband can be associated with ARCL [McKusick, 1972;Van Maldergem et al, 1988] but is extremely rare in ADCL where only two cases have been reported [Hayden et al, 1968;Tassabehji et al, 1998]. Pulmonary artery stenosis is frequently associated with ELN haploinsufficiency [Metcalfe et al, 2000].…”
Section: Discussionmentioning
confidence: 82%
“…[22][23][24] Compared with ADCL, ARCL-I is more often associated with severe systemic complications, especially emphysema and diaphragmatic defects, arterial tortuosity, and aneurysms (Fig 4, D and E ). 23,25,26 Joint laxity and muscular hypotonia is also observed (Fig 4, C ). Many patients die from pulmonary or cardiac complications in early childhood 23,25,26 Mental and motor development are usually normal.…”
Section: Inherited Forms Of CLmentioning
confidence: 77%
“…23,25,26 Joint laxity and muscular hypotonia is also observed (Fig 4, C ). Many patients die from pulmonary or cardiac complications in early childhood 23,25,26 Mental and motor development are usually normal. 22,27,28 Etiology.…”
Section: Inherited Forms Of CLmentioning
confidence: 77%
“…This combination of anomalies, plus a fatal outcome in infancy, reported in all but one informative cases, and a negative family history in 17 of 17 cases negate the diagnoses of Marfan syndrome and/or congenital contractural arachnodactyly. A severe form of cutis laxa with pulmonary emphysema and a poor outcome has also been described, but signs of a marfanoid phenotype have never been reported in these patients (Agha et al 1978;Van Maldergem et al 1988). On the other hand, the above mentioned cases and the present report have many features in common, which could define a new syndrome that we have coined as neonatal cutis laxa with a marfanoid phenotype.…”
Section: Discussionmentioning
confidence: 38%